Detoxification of hazelnuts by different cold plasmas and gamma irradiation treatments. (June 2019) - Sen, Yasin; Onal-Ulusoy, Baran; Mutlu, Mehmet
Abstract: The detoxification effects of cold atmospheric-pressure (AP, 3000 L/h of air, 25 kHz, 655 W-1.7 min) and low-pressure (LP, air-100 W-30 min) plasmas and gamma irradiation(GMI, 10 kGy-10 min) treatments on different concentrations of pure aflatoxin B1(AFB1) and AFB1 + B2 (TotAFs) as well as same toxins spiked on hazelnut were investigated. Both plasmas reduced 72–73% of AFB1 (3 ppb) spiked on hazelnuts while GMI reduced 47% of AFB1. TotAFs (6 ppb) reductions on hazelnut after both plasmas were 70–71%, which was also higher than that of GMI (15.5%). However, the reductions in pure AFB1 at 1–50 ppb and TotAFs at 1.03–51.5 ppb after GMI (97–100%) were higher than those of AP (55–75%) and LP (69–90%) plasmas. AP plasma has the potential to be an alternative to conventional detoxification methods because it is both effective on aflatoxins in foods and maintains the sensory attributes of food evaluated by a sensory panel. Industry relevance: The use of plasma technology in foods for detoxification purposes is an economic alternative to conventional and other non-thermal processes as well as meeting the industry's demand for sustainable development. This study showed that different cold plasmas are capable of reducing the aflatoxins as pure forms as well as in food. The results contributed to the understanding of cold plasma detoxification effects on aflatoxins and could be a basis for a possible industrial implementation. Highlights: Aflatoxin (AFB1, AFB2) detoxification efficacy of cold plasmas and gamma irradiation (GMI) treatments were evaluated. AFB1 spiked on hazelnut, AFB1 in pure form, and AFB1 coexisted with AFB2 were affected differently. Cold plasma treatments reduced 70–73% of spiked AFB1 (3 ppb) and AFB1 (5.8 ppb) located with AFB2 (0.2 ppb). GMI treatment reduced 48–100% of pure AFB1 (1–1000 ppb) and AFB1 (1–1000 ppb) located with AFB2 (0.03–30.9 ppb). Atmospheric-pressure cold plasma and GMI treatments maintained sensory attributes of hazelnut.